Solvent-controlled quadruple catenation of giant chiral (8+12) salicylimine cubes driven by weak hydrogen bonding [data] - Wagner, Philippe; Rominger, Frank; Gross, Jürgen H.; Mastalerz, Michael (Universität, 2023)
A quadruply interlocked catenane has been formed from giant chiral [8+12] salicylimine cubes in a reaction that can be controlled by the reaction solvent. Single-crystal X-ray diffraction revealed hydrogen bonding to be a central driving force for the catenation. Furthermore, scrambling experiments with partially deuterated cages allowed mechanistic insights into the interlocking process.